Mengukur kinerja keuangan dan profitabilitas pada btpn syariah periode 2019 – 2023 - Anggrainie, Agustina; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to evaluate the financial performance and profitability of Bank BTPN Syariah during the period from 2019 to 2023. BTPN Syariah operates based on Islamic principles and focuses on Islamic banking in Indonesia. To assess its performance, an analysis was conducted on several profitability ratios, such as Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results show that, despite some fluctuations in these ratios, the overall performance of the bank remains positive. NPM saw a significant increase in 2020 and 2021 but declined in 2023, which requires further attention. Meanwhile, both ROA and ROE showed a positive trend, with ROE remaining stable at 12.3% in 2023. The performance decline in 2023 indicates the need for a deeper analysis to identify areas for improvement. The study suggests that the bank should further develop its digital services and review its equity usage strategy to enhance profitability in the future.